Deciphering Myostatin’s Regulatory, Metabolic, and Developmental Influence in Skeletal Diseases - Omosule, Catherine L.; Phillips, Charlotte L. (Frontiers in Genetics, 2021)
Current research findings in humans and other mammalian and non-mammalian species support the potent regulatory role of myostatin in the morphology and function of muscle as well as cellular differentiation and metabolism, with real-life implications in agricultural meat production and human disease. Myostatin null mice (mstn-/-) exhibit skeletal muscle fiber hyperplasia and hypertrophy whereas myostatin deficiency in larger mammals like sheep and pigs engender muscle fiber hyperplasia. Myostatin’s impact extends beyond muscles, with alterations in myostatin present in the pathophysiology of myocardial infarctions, inflammation, insulin resistance, diabetes, aging, cancer cachexia, and musculoskeletal disease. In this review, we explore myostatin’s role in skeletal integrity and bone cell biology either due to direct biochemical signaling or indirect mechanisms of mechanotransduction. In vitro, myostatin inhibits osteoblast differentiation and stimulates osteoclast activity in a dose-dependent manner. Mice deficient in myostatin also have decreased osteoclast numbers, increased cortical thickness, cortical tissue mineral density in the tibia and increased vertebral bone mineral density. Further, we explore the implications of these biochemical and biomechanical influences of myostatin signaling in the pathophysiology of human disorders that involve musculoskeletal degeneration. The pharmacological inhibition of myostatin directly or via decoy receptors has revealed improvements in muscle and bone properties in mouse models of osteogenesis imperfecta, osteoporosis, osteoarthritis, Duchene muscular dystrophy and diabetes. However, recent disappointing clinical trial outcomes of induced myostatin inhibition in diseases with significant neuromuscular wasting and atrophy reiterate complexity and further need for exploration of the translational application of myostatin inhibition in humans.